Becoming Visible: Uncovering hidden entanglements of power, performativity and becoming subjectivities in a global bank. Issue 12 (December 2021) - Beavan, Katie
This paper explores entanglements and flows of power, performativity and related becoming subjectivities, in a rich thicket of lived experience in a global bank. The inquiry focuses on an affective auto/ethnographic field text of a mundane, cross-continent, telephone meeting between a senior executive colleague and myself. Experimenting with post-qualitative, transversal, feminist inquiry 'I' deliberately plug into multiple, criss-crossing, philosophical concepts of gendered power, performativity and subjectivity. 'I' playfully–vulnerably assay with new ways of doing processual organizational research and making knowing–as–action, including with potential readers. 'I' write differently, aiming to enact and exemplify the post-qualitative organization studies terrain as unsettled, unsettling and unpredictable. In a processual, abductive interpretation of my field text 'I' uncover agential subjectivities emerging from unconscious affective entanglements travelling across continents and disjunctive temporalities and between human and non-human entities. 'I' depart by reflecting on the contributions of my paper and implications of this inquiry for my practice as an organization studies practitioner–researcher.